The Tyrrhenian Intermediate Water (TIW): Characterization and formation mechanisms. (January 2019) - Napolitano, Ernesto; Iacono, Roberto; Ciuffardi, Tiziana; Reseghetti, Franco; Poulain, Pierre-Marie; Notarstefano, Giulio
Highlights: The properties of the Tyrrhenian Intermediate Water (TIW) are investigated. Argo float, XBT, and dissolved oxygen data are used to characterize the TIW. Data and model simulations are used to illustrate the TIW formation process. TIW outflow is shown to affect the hydrology of the Western Mediterranean. Recent changes in the TIW properties are highlighted, due to warming effects. Abstract: This work focuses on the Tyrrhenian Intermediate Water, a water mass present in the Tyrrhenian Sea (Western Mediterranean Sea), which approximately lies between 100 m and 200 m of depth, and is characterized by a local minimum of temperature. Here, for the first time, a thorough investigation of the Tyrrhenian Intermediate Water has been performed, based on the analysis of long time series of observations (XBT, Argo float, dissolved oxygen data) and on modeling results. It was found that this water is present in a large part of the Tyrrhenian basin, and is a persistent feature of the basin hydrology. It is formed by winter convection, with some differences between the southern part of the basin and the northern part, where strong winter cooling produces deeper convection and mixing. The process of formation of the Tyrrhenian Intermediate Water has been investigated in detail, through the analysis of the experimental datasets, of dedicated numerical experiments with a one-dimensional mixed layer model, and of the outputs of a three-dimensional ocean circulation model. Such analysis has excluded remote contributions from intermediate waters produced in the western portion of the Western Mediterranean basin. On the other hand, the presence of the Tyrrhenian Intermediate Water has been found to impact not only the Tyrrhenian Sea hydrology, but also that of the adjacent Liguro-Provençal basin, because this water mass outflows from the Corsica Strait, and is transported as far as the Gulf of Lion, in the core of the region where deep waters are formed. Recent changes in the properties of this intermediate water mass have also been highlighted, which result from the warming of the neighboring water layers.